Ecotourism as Leisure and Labor in the Experience of the “Great” Outdoors - Sowards, Stacey K.; Banerjee, Paulami (Frontiers in Communication, 2021)
Ecotourism as an international concept promotes foreign and domestic tourism to locations in forests, oceans, and other forms of the natural world. National parks and other preserved ecosystems are popular destinations, usually located in the so-called developing countries or Global South countries, such as South and Southeast Asia, Central and South America, and Africa. This paper examines the construction of labor and leisure as forms of experience of the "Great Outdoors" for both ecotourist and local peoples. We argue that ecotourism is a form of colonial/racialized/gendered gaze, in which power imbalances are reflected in people's experiences of ecotourism as labor and leisure. We use case studies in Indonesia and India, based on our long standing field research in each respective country.